Clinical Evaluation of a MassCode PCR Assay for the Syndromic Detection of Pathogens that cause Respiratory Disease - Smith, D.; Yang, L.; Moody, K.; Williams, David; Basehore, S.; Novoradovskaya, N.; McInnes, R.; Monell, C.; Fischer, G. (International Union of Microbiological Societies, 2011)
MassCode PCR is a novel technology for the rapid, sensitive and simultaneous detection of multiple gene sequences. This technique utilises a library of molecular tags, each unique in its molecular weight. MassCode tags are conjugated to oligonucleotide primers using a UV-cleavable linker that enables separation of primer and tag. Different primers are labelled each with a different molecular weight tag and are used to amplify target nucleic acids in a multiplex RT-PCR. After removing unincorporated primers, tags are released by UV irradiation and analysed using a single quadrupole liquid chromatography mass spectrometer (LC/MS). Thus, amplification of the gene target produces a unique dual signal in LC/MS analysis that allows its identification. Respiratory disease represents a diagnostic challenge, with multiple microbial agents associated with infection, and co-infection frequently observed. We have evaluated a commercial multiplex (28-plex) MassCode PCR assay developed by Agilent Technologies to detect viral pathogens, including types or subtypes of coronavirus, metapneumovirus, parainfluenza virus, influenza virus, respiratory syncytial virus, enterovirus and rhinovirus, as well important bacterial and fungal pathogens that infect the airways. The performance of this assay was evaluated in a clinical diagnostic laboratory using clinical specimens obtained from the upper and lower respiratory tract from human cases of disease in Western Australia. The performance of the MassCode assay was compared to established in-house (RT-)PCR assays. Our findings indicate that MassTag PCR offers an inexpensive and sensitive diagnostic platform suitable for high-throughput testing.